Correlation of pharmacokinetic dispositionof methotrexate and serum cytokine levels in rheumatoid arthritis patients - Aringazina, Raisa; Myasoutova, Leysan; Babaskina, Liudmila; Pashanova, Olga (Bangladesh Journal of Medical Science, 2022)
Objective: Methotrexate is the principal basic anti-inflammatory medication used in the rheumatoid arthritis treatment.Therefore, research into its effect on cytokine concentrations may help improve the effectiveness of disease treatment. Study aim: was to investigate the neffect of methotrexate therapy on the blood content of proinflammatory cytokines in RA patients, as well as define the relation of proinflammatory cytokine blood concentration to clinical and laboratory disease features and methotrexate pharmacokinetics. Material and methods: Sixty-five patients with rheumatoid arthritis (46 women and 19 men; average age 50.83± 8.91 years) underwent an examination.Thirty-two patients (26 women and 6 men) participated in studyingmethotrexate pharmacokinetics. Results and Discussion: The course of rheumatoid arthritis is accompanied by a significant increase of TNF-α (40.36±4.01 pg/ml), IL-1β (17.68±1.74 pg/ml), andIL- 6(8.39±0.46pg/ml) in the blood.Oral administration of methotrexate (MT) for patients with rheumatoid arthritis promotes persistent elimination of clinical disease symptoms and reduced production of proinflammatory cytokines:TNF-α drops by 2.08 times (p<0.05) compared to baseline, that of IL-1β and IL-6 – by 2.86 (p<0.05) and2.84times(p<0.05), correspondingly.Blood levels for TNF-α and IL-6 are consistent with clinical markers for rheumatoid arthritis, such as joint pain, joint swelling, and morning stiffness in extremities.Blood cytokine concentrations were not correlated with AUC, Cmax, and Tmax. There was an inverse correlation between the blood rates of TNF-α and the weekly dose of MT (r = -0.34, p<0.05) and II-6 and the weekly dose of MT (r = -0.32, p<0.05). Conclusion: Rheumatoid arthritis is closely associated with increaseing of proinflammatory cytokine blood levels, which affects the clinical course of the disease.The dosage of methotrexate applied affects the blood concentrations of IL-6 and TNF-α. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 335-343